PEMBERDAYAAN MASYARAKAT DESA MELALUI EDUWISATA DAN EKOWISATA - Rahmat; Maulidatul Khoiriyah (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2023)
The aim of the service activities is to innovate in empowering tourism villages Tanjungan Village, edutourism and ecotourism is able to boost the wheels of a new economy for the Tanjungan community in particular. The method used in this service is Participatory Action Research or what is often called PAR with the approach used is problem solving and participation, because it is considered the most relevant to community empowerment efforts. The results of service activities in Tanjungan Village, Kemlagi District, Mojokerto Regency include 1) Implementation of edutourism in the form of transformative leadership training for Karangtaruna youth and 2) Ecotourism assistance, including a) A book on the history of Tanjungan Village has been published, b) There is a documentary video of silver handicrafts, c) Reforestation of tourist attractions and d) Production of typical Tanjungan Village merchandise. This activity is also for branding and developing Tanjungan Village as a tourist village as well as innovation to stimulate the economy.